2021
DOI: 10.1155/2021/6623792
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Lidocaine Alone versus Lidocaine plus Dexmedetomidine in Impacted Third Molar Extraction Surgery, a Double-Blind Randomized Control Trial for Postoperative Pain Evaluation

Abstract: Objectives. Administration of medications such as dexmedetomidine as a topical anesthetic has been suggested in the pain control in dentistry. This double-blind randomized control trial study evaluated postoperative pain and associated factors following impacted third molar extraction surgery. Lidocaine alone was taken as the control and lidocaine plus dexmedetomidine as the intervention. Materials and Methods. Forty patients undergoing mandibular third molar extraction entered the study and were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Also, according to Tonooka and colleagues, administration of DEX added to LIDO for dental local anesthesia in eight patients led to improved sedation levels and enhanced pulpal local anesthesia compared to LIDO alone [ 34 ]. Similar results were obtained from other clinical studies by Alizargar, Sing, and colleagues [ 35 , 36 ]. These results are consistent with the outcomes of our study and support the idea that DEX, regardless of the route of administration, could provide superior results concerning the level of sedation and patients' cooperation.…”
Section: Discussionsupporting
confidence: 91%
“…Also, according to Tonooka and colleagues, administration of DEX added to LIDO for dental local anesthesia in eight patients led to improved sedation levels and enhanced pulpal local anesthesia compared to LIDO alone [ 34 ]. Similar results were obtained from other clinical studies by Alizargar, Sing, and colleagues [ 35 , 36 ]. These results are consistent with the outcomes of our study and support the idea that DEX, regardless of the route of administration, could provide superior results concerning the level of sedation and patients' cooperation.…”
Section: Discussionsupporting
confidence: 91%
“…Many methods for sedation are being used for third molar impactions. All these methods aim to achieve better patient outcomes in terms of pain control as noted in other studies [ 26 ]. Also, patients presenting with periodontal disease with higher anxiety levels, while undergoing scaling and root planning treatments may exhibit negative clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a randomized controlled trial study, Yamane et al showed that co-administration of dexmedetomidine and lidocaine considerably boosted the local anesthetic strength of lidocaine without any major influences on the cardiovascular system when locally injected into the oral mucosa [56]. Moreover, in dentistry, the co-administration of dexmedetomidine and lidocaine blocked the maxillary and mandibular nerve and significantly prolonged the block duration and shortened the onset of action, as well as the need for fewer analgesics in the postoperative period [59,60].…”
Section: Discussionmentioning
confidence: 99%